2016
DOI: 10.18632/oncotarget.12019
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulated resistin level in consequence of decreased neutrophil counts in untreated Grave's disease

Abstract: Resistin, belongs to cysteine-rich secretory protein, is mainly produced by circulating leukocytes, such as neutrophils monocytes and macrophages in humans. To date, few but controversial studies have reported about resistin concentrations in hyperthyroid patients, especially in Graves' disease (GD). We undertaked a controlled, prospective study to explore the serum resistin concentration in GD patients before and after -MMI treatment. In addition, we also investigated the main influencing factor on serum resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
2
11
0
2
Order By: Relevance
“…We detected resistin secretion by neutrophils, but not by monocytes, and this secretion increased upon activation. In line with our findings, resistin has been shown to be secreted by circulating neutrophils in patients with Graves’ disease and sepsis …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We detected resistin secretion by neutrophils, but not by monocytes, and this secretion increased upon activation. In line with our findings, resistin has been shown to be secreted by circulating neutrophils in patients with Graves’ disease and sepsis …”
Section: Resultssupporting
confidence: 92%
“…We detected resistin secretion by neutrophils, but not by monocytes, 27,28 and this secretion increased be secreted by circulating neutrophils in patients with Graves' disease and sepsis. 29,30 To identify whether the factors responsible for resistin production were also responsible for IL-6 production, we analyzed whole blood cultures stimulated with different inflammatory cytokines.…”
Section: Induction Of Resistin and Il-6mentioning
confidence: 99%
“…Van der Weerd K and et al reported that with fl ow cytometry method analysis, T and B lymphocyte counts were signifi cantly higher in Graves' disease than in healthy control group and in the same study there was a positive correlation between the levels of ft4 and B lymphocytes (14). Although antithyroid drugs are known to cause neutropenia as a side effect (15), Peng Y and et al, reported that compared with untreated Graves' patients, neutrophil counts increase in Graves patients who are euthyroid with treatment (16). In this study neutrophil count increased but not statistically signifi cantly.…”
Section: Discussionmentioning
confidence: 71%
“…These studies were published between 1932 and 2019 by authors from USA, Scotland, New Zealand, Italy, Middle East (ie Turkey and Iran), Asia (ie Japan and China) and UK. They were monocentric, observational cohort studies, with retrospective design except for two which were prospective 13,17 . The total number of untreated hyperthyroid patients, whose baseline ANC values or neutropenic cases were available, was 1144 [including 991 affected by Graves’ disease and 153 with other causes of hyperthyroidism (ie toxic multinodular goitre and toxic adenoma)].…”
Section: Resultsmentioning
confidence: 99%